NUMERICAL ANALYSIS OF CRACK CONCENTRATION AND PROPAGATION IN REINFORCED CONCRETE DEEP BEAMS WITH VARYING ATTRIBUTES - Sangeeth sulphi, (International Journal of Innovations in Engineering Research and Technology, 2021)
Cracks in concrete beams are due to an increase in shear stress appearing near the support such as wall or column. These cracks are called shear crack and are inclined at 45 degrees with the horizontal. These cracks in beams can be avoided by providing additional shear reinforcements near the support where the shear stress is maximum. Deep beams are structural elements loaded as simple beams in which a significant amount of the load is carried to the supports by a compression force combining the load and the reaction. As a result, the strain distribution is no longer considered linear, and the shear deformations become significant when compared to pure flexure. Deep beam is a beam having large depth/thickness ratio and shear span depth ratio less than 2.5 for concentrated load and less than 5.0 for distributed load. The study intended to investigate the crack development, propagation, and merging behaviour of critical shear cracks. For this, certain parameters like shear span to depth ratio, location of opening (if provided), presence of skin reinforcement and shear reinforcement should be varied. For the purpose of analysing crack concentration in deep beam, ABAQUS Finite Element Analysis software is suited.